Advanced Nanotechnology-Based Nucleic Acid Medicines - Noriko Miyamoto; Mina Sakuragi; Yukio Kitade (Pharmaceutics)
Nucleic acid medicines are a highly attractive modality that act in a sequence-specific manner on target molecules. To date, 21 such products have been approved by the Food and Drug Administration. However, the development of nucleic acid medicines continues to face various challenges, including tissue and cell targeting as well as intracellular delivery. Numerous research groups are addressing these issues by advancing the development of nucleic acid medicines through nanotechnology. In countries other than Japan (including Europe and the USA), >40 nanotechnology-based nucleic acid medicines have been tested in clinical trials, and 15 clinical trials are ongoing. In Japan, three phase I trials are ongoing, and future results are awaited. The review summarizes the latest research in the nanotechnology of nucleic acid medicines and statuses of clinical trials in Japan, with expectations of further evolutions.